The effect of financial literacy and demographic variable on behavioral biases - Murhadi, Werner Ria; Frederica, Devina; Marciano, Deddy (Asian Economic and Financial Review, 2024)
The current research investigates the association between demographic factors, including financial knowledge and demographic characteristics like gender, occupation, age, education, and income, and investor behavior biases, including bias against overconfidence, disposition effect, and herding bias. Further enhancement of behavioural finance research is required in Indonesia. This study applied a quantitative analysis technique called structural equation modeling. Stock investors aged 17 and 40 were given questionnaires for this study. Respondent data collection was carried out by distributing questionnaires through several social media sites, such as Line, WhatsApp, and Instagram, to members of the investor’s community. The total number of respondents obtained from distributing this questionnaire was 170. According to the study, overconfidence bias significantly affects income and financial literacy. However, overconfidence bias does not affect gender, occupation, investment experience, education, or age. Furthermore, for behavioral biases, the disposition effect does not affect financial literacy or all demographic factors. Finally, for herding behavior bias, bias significantly affects financial literacy, investment experience, and income, but herding bias does not affect gender, occupation, education, age, or income. These results have implications for investors with a high level of financial literacy, which will help them determine rational investment decisions. This research also has implications for high-income investors who tend not to follow herding behavior.